2023
DOI: 10.1002/ctm2.1250
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss potentiates Th17‐cell pathogenicity and promotes autoimmune uveitis

Abstract: Background Sleep loss (SL) is a health issue associated with the higher risk of autoimmune and inflammatory disorders. However, the connection between SL, the immune system, and autoimmune diseases remains unknown. Methods We conducted mass cytometry, single‐cell RNA sequencing, and flow cytometry to analyze how SL influences immune system and autoimmune disease development. Peripheral blood mononuclear cells from six healthy subjects before and after SL were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Under the stimulation of IL-23, the receptor IL-23R on the surface of CD4 + T cells transmits signals to promote Th17 cells differentiation and Th17's secretion of IL-17, GM-CSF and other pathogenic cytokines. Targeting GM-CSF inhibits Th17 cell pathogenicity and attenuates EAU severity [ 46 ]. Flow cytometry indicated that the proportion of IL-23R + and GM-CSF + Th17 cells increased by addition of IL-23, and decreased after PRG treatment (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under the stimulation of IL-23, the receptor IL-23R on the surface of CD4 + T cells transmits signals to promote Th17 cells differentiation and Th17's secretion of IL-17, GM-CSF and other pathogenic cytokines. Targeting GM-CSF inhibits Th17 cell pathogenicity and attenuates EAU severity [ 46 ]. Flow cytometry indicated that the proportion of IL-23R + and GM-CSF + Th17 cells increased by addition of IL-23, and decreased after PRG treatment (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intimate association between sleep and the immune system suggests that SD may result in immune dysregulation ( 35 ). Murine models have shown that SD can influence the signaling of GM-CSF (Granulocyte-Macrophage Colony-Stimulating Factor) by regulating Th17 and activated CD4 T cells ( 36 ), which in turn interacts with myeloid cells, exacerbating the progression of autoimmune diseases. Simple sleep deprivation in rats has been found to increase Natural Killer (NK+) and T cells (CD8+) in the spleen and decrease B cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, in the recently published article in Clinical and Translational Medicine , Liu et al 9 . simulated the condition of SL in humans and established the sleep deprivation model in mice to explore the effects of SL on immune system and EAU development.…”
Section: Commentarymentioning
confidence: 99%
“…To this end, in the recently published article in Clinical and Translational Medicine, Liu et al 9 simulated the condition of SL in humans and established the sleep deprivation model in mice to explore the effects of SL on immune system and EAU development. Based on singlecell mass cytometry by time of flight (CyTOF) and singlecell RNA sequencing (scRNA-seq), they firstly constructed an immune cell atlas of SL according to the effect of SL on healthy individuals and mice.…”
Section: Commentarymentioning
confidence: 99%